La escuela como sujeto colectivo en el conflicto armado: el caso de la comunidad educativa de Villanueva (Valencia, Córdoba) abordado desde un enfoque de memoria histórica (2021)
In the last years, there has been a surge in research focused on understanding the dynamics and impact of the armed conflict in the state of Córdoba, Colombia. Likewise, at the national level, there seems to be greater awareness on the importance of enhancing our understanding of how the armed conflict has particularly affected school communities. However, this continues to be an under-researched filed, with almost no precedents in Córdoba. This research intents to respond to this void through a study focused on the rural school community of Villanueva, Valencia. Moreover, this research offers conceptual and methodological innovations in the sense that it suggests that schools should be understand as “collective subjects”. Methodologically, the research involves two levels: the author‟s involvement in a participatory research related to collective memory, and an analysis carried out through a historical memory approach. The study concludes that the Villanueva school community has been affected in multiple ways and that its collective action repertoires can be understood as examples of resilience but not of resistance. Likewise, this work argues that Villanueva should not be understood as an isolated case, but rather as a case that is representative of the logics of paramilitary social control, whereby, while blood was being spilled and terror was imposed, some communities in Colombia were captured by them and received material benefits as part of a strategy of legitimation and territorial control.